Prevalence of Stress and Anxiety among Oral Healthcare Workers during COVID-19 Pandemic: Cross-Sectional Study - Deo, Saroj Prasad; Goit, Bharat Kumar; Baral, Dharnidhar (Med Phoenix, 2023)
Introduction: The COVID-19 pandemic has significantly affected oral health care workers’ lives in all dimensions. They face mental health challenges due to public health actions, such as physical distancing and quarantine, which can make us feel isolated and lonely and increase stress and anxiety. This study aimed to find the prevalence of stress and anxiety among online respondent oral healthcare workers during the COVID-19 pandemic. Materials and Methods: This prospective descriptional cross-sectional study was conducted from 24 June 2020 to 13 July 2020 among oral health care workers in a tertiary care centre. Ethical approval was taken from the Ethical Review Board (Reference number: 2710). A convenience sampling method was used. The data were collected using a questionnaire through Google Forms. Point estimate and 95% Confidence Interval were calculated. Results: Among 133 oral health care workers, the prevalence of anxiety and stress was found to be 32(24.06%) (17.96 30.16 at 95% Confidence Interval) and s 11(8.27 %) (4.34 12.20, 95% Confidence Interval), respectively. Conclusion: The prevalence of anxiety among oral health care workers was slightly lower, but higher stress was observed than in similar studies done in similar settings and methods. Further research in this field is needed.